PENGARUH KREDIBILITAS ENDORSER AGNES MONICA DALAM IKLAN KARTU PRABAYAR SIMPATI DI TELEVISI TERHADAP MINAT BELI KONSUMEN - Bahqrin Sartika; Ign Sukirno (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
This study aims to determine consumers’ assessment of the credibility of the endorser Agnes Monica and diferences in terms of assessment based on gender diferences and the amount of pocket money a student / month and determine the infuence of Agnes Monica credibility endorser in ads on television sympathy prepaid cards to consumers to buy. The sampling method used is a method porpusive sampling. Sample in this study were 100 respondents who are consumers who never saw Agnes Monica in prabyar sympathy card advertisement on television. To test this hypothesis, used four methods of analysis is Mean Arithmetic, One Sample t-test, independent sample T-test and Multiple Linear Regression Analysis. Results of Mean arithmetic of consumer ratings of variable attractiveness and good expertise while for variable trustworthiness is pretty good. Results of analysis Independent Sample T-test there was no diference consumer ratings were reviewed based on gender diferences. Meanwhile, when the review is based on the diference in the amount of student’s money per month showed diferences in consumer ratings for the variable expertise. Multiple Linear Regression analysis results that there is a signifcant and positive efect on the variable trustworthiness and expertise and there is no signifcant negative infuence and attractiveness to the variable.Keywords: celebrity endorser credibility, attractiveness, trustworthiness, expertise, buying interest.